ENCOURAGING DAILY ENGLISH SPEAKING TO BOOST STUDENTS’ CONFIDENCE - Sri Ariani (Sinar Lima, 2025)
This research aims to find out does the implementation of daily English speaking activities increase students’ confidence in speaking English? It is focused on implementation a structured program of daily speaking activities designed to create a supportive learning environment where students can practice and improve their speaking skills without the fear of judgment. The study involved 50 students of the second semester students of English Department of Mandalika University of Education. Over a semester, participants engaged in various speaking activities, including pair conversations, group discussions, and role-playing scenarios. Data were collected through pre- and post-program surveys, measuring students' self-reported confidence levels and fluency in English speaking. Results indicated a significant increase in student confidence, with the percentage of students feeling assured in their speaking abilities rising from 30% to 70% after the program. Additionally, qualitative feedback revealed that students valued the opportunity to practice speaking regularly and reported a decrease in anxiety associated with language use. This research highlights the importance of integrating daily speaking practices into language education curricula to foster a positive learning atmosphere. By encouraging active participation and providing consistent opportunities for speaking, educators can help students overcome barriers to communication, thus enhancing their overall language proficiency and confidence.